2015
DOI: 10.1111/apa.13069
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life may deteriorate from adolescence to young adulthood after extremely preterm birth

Abstract: Our comparison of EPB and TB subjects at the ages of 17 and 24 indicated that psychosocial HRQoL may deteriorate for EPB subjects when they enter adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 27 publications
2
31
1
6
Order By: Relevance
“…With this exception, only data available in the publications were used in this review. From one paper, 4 we calculated combined means and standard deviations, as the results it presented were broken down by subgroups. No decisions were made a priori on how to deal with obtaining additional information from authors.…”
Section: Methodsmentioning
confidence: 99%
“…With this exception, only data available in the publications were used in this review. From one paper, 4 we calculated combined means and standard deviations, as the results it presented were broken down by subgroups. No decisions were made a priori on how to deal with obtaining additional information from authors.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that differences and changes in quality of life and HRQoL between preterm and term groups are small, are not necessarily observed by self‐reports and diminish over time . However, four longitudinal studies from 2015 to 2016 challenged this view by showing constantly lower levels of HRQoL in adults born very or extremely preterm, before 32 or 28 weeks of gestation, respectively, or with an extremely low birth weight of <1000 g. This even applied to adults who were not impaired . Although many of the outcomes of preterm birth differ by sex or intrauterine growth , few studies have assessed whether those two factors also have an impact on HRQoL and that was the aim of our study.…”
mentioning
confidence: 99%
“…13 However, most studies were based on measuring health statuses instead of QOL in this review. The Child Health Questionnaire (CHQ) was used in two studies 18,37 ; however, this assessment includes health status and functioning and may not be appropriate for measuring HRQOL in children with disabilities. Therefore, almost no information regarding parent-reported HRQOL of adolescents who were born extremely prematurely exists for comparison with our data.…”
Section: Discussionmentioning
confidence: 99%